Young Cam Jansen and the library mystery - Adler, David A, 1947-; Natti, Susanna (New York : Viking, 2001)
Cam uses her photographic memory to find a shopping list that her dad lost at the library.
"Ages 5-8"--Cover p.[4].
"Grades K-2"--Cover p.[4].
"Beginning to read"--Cover p.[4].
Booklist, May 2001.
Booklist.
2.4
Keywords: Jansen, Cam (Fictitious character) -- Juvenile fiction; Memory -- Juvenile fiction; Memory -- Fiction; Mystery and detective stories; Memory -- Fiction; Mystery fiction; Memory -- Fiction; Mystery and detective stories; Mystery fiction